Coupled Effects of Water and Low Temperature on Quasistatic and Dynamic Mechanical Behavior of Sandstone - Zilong Zhou; Yude E; Xin Cai; Jing Zhang (Geofluids)
The mechanical behavior of rock materials is critically affected by water and temperature. To comprehensively study the coupled effects of water saturation and low temperature on the mechanical properties of sandstone, both quasistatic and dynamic compressive tests were performed on dry and water-saturated specimens under room temperature and -60°C. The results indicated that under the same strain rate, at room temperature, the compression strength and elastic modulus of the sandstone specimen are significantly reduced when the specimen becomes water-saturated. However, at -60°C, the compression strength and elastic modulus of the dry specimen notably increase compared to that at room temperature. Interestingly, these mechanical parameters of the saturated-frozen specimen are lower than that of the dry one but slightly higher than that of the saturated specimen under room temperature. Moreover, regardless of temperature, the saturated specimens have a higher strain rate dependence in terms of strength. The dual effects of water and subzero temperature of the mechanical behavior of rock are discussed.